Pengaruh Produk Halal terhadap Loyalitas Pelanggan pada Industri Makanan - Priya Mitra Cahya Jaweda; Donny Darmawan (Aksioreligia, 2025)
This study analyzes the influence of halal products on customer loyalty in the food industry. The presence of halal products has become a strategic concern as consumer awareness and demand for products that comply with Islamic principles continue to increase. The purpose of this study is to examine the extent to which halal product attributes contribute to customer loyalty. The research employed a survey method by distributing questionnaires to consumers of halal food products as respondents. The collected data were analyzed using inferential statistical techniques. The results show an R Square value of 0.757, indicating that 75.7% of the variation in customer loyalty can be explained by the halal product variable, while the remaining 24.3% is influenced by other factors outside the research model. The regression coefficient of 0.927 demonstrates that an increase in halal product attributes has a significant positive effect on customer loyalty. These findings emphasize the importance of implementing halal principles as a key factor in building and maintaining consumer loyalty within the food industry.